Synthesis of α-l-Fucopyranoside-Presenting Glycoclusters and Investigation of Their Interaction with Photorhabdus asymbiotica Lectin (PHL) - Jančaříková, Gita; Herczeg, Mihály; Fujdiarová, Eva; Houser, Josef; Kövér, Katalin E; Borbás, Anikó; Wimmerová, Michaela; Csávás, Magdolna (Chemistry (Weinheim an der Bergstrasse, Germany), 2018)
Photorhabdus asymbiotica is a gram-negative bacterium that is not only as effective an insect pathogen as other members of the genus, but it also causes serious diseases in humans. The recently identified lectin PHL from P. asymbiotica verifiably modulates an immune response of humans and insects, which supports the idea that the lectin might play an important role in the host-pathogen interaction. Dimeric PHL contains up to seven l-fucose-specific binding sites per monomer, and in order to target multiple binding sites of PHL, α-l-fucoside-containing di-, tri- and tetravalent glycoclusters were synthesized. Methyl gallate and pentaerythritol were chosen as multivalent scaffolds, and the fucoclusters were built from the above-mentioned cores by coupling with different oligoethylene bridges and propargyl α-l-fucosides using 1,3-dipolar azide-alkyne cycloaddition. The interaction between fucoside derivates and PHL was investigated by several biophysical and biological methods, ITC and SPR measurements, hemagglutination inhibition assay, and an investigation of bacterial aggregation properties were carried out. Moreover, details of the interaction between PHL and propargyl α-l-fucoside as a monomer unit were revealed using X-ray crystallography. Besides this, the interaction with multivalent compounds was studied by NMR techniques. The newly synthesized multivalent fucoclusters proved to be up to several orders of magnitude better ligands than the natural ligand, l-fucose.
Keywords: molekulární konformace; Ligands; agglutination; Molecular Conformation; Humans; ligandy; Photorhabdus asymbiotica; glykosidy; fucoclusters; krystalografie rentgenová; lektiny; vazebná místa; lidé; Crystallography, X-Ray; fukosa; Fucose; Binding Sites; multivalency; Lectins; Glycosides; Photorhabdus; lectin